Assessing the 'Small Population' Paradigm: The Effects of Stochasticity on Evolutionary Change and Population Growth in a Bird Metapopulation - Yimen G. Araya‐Ajoy; Tor Hansson Frank; Hamish Burnett; Jørgen S. Søraker; Peter S. Ranke; Debora Goedert; Thor‐Harald Ringsby; Henrik Jensen; Bernt‐Erik Sæther (Ecology Letters, 2025)
Habitat loss is leading to smaller fragmented populations, increasing their susceptibility to stochasticity. Quantifying the effects of demographic and environmental stochasticity on population dynamics and the contribution of selection versus drift to phenotypic change is essential to assess the potential consequences of environmental change. We examined how stochasticity influenced population growth and body mass changes over 22 years in 11 insular house sparrow ( Passer domesticus ) populations. Environmental stochasticity induced synchrony in growth rates across populations while also causing substantial island‐specific fluctuations. Additionally, demographic stochasticity led to larger annual growth rate fluctuations in smaller populations. Although heavier individuals generally had higher fitness, we detected non‐directional evolutionary change in body mass, driven by drift rather than selection. Our study provides a unique quantitative assessment of the ‘small population’ paradigm, highlighting the importance of theoretically driven analyses of long‐term individual‐based data to understand the drivers of phenotypic evolution and a population's long‐term viability.

Population origin and heritable effects mediate road salt toxicity and thermal stress in an amphibian - Lauren M. Conner; Debora Goedert; Sarah W. Fitzpatrick; Amber Fearnley; Emma L. Gallagher; Jessica D. Peterman; Mia E. Forgione; Sophia Kokosinska; Malik Hamilton; Lydia A. Masala; Neil Merola; Hennesy Rico; et al. (Chemosphere, 2024)

The genetic basis of dispersal in a vertebrate metapopulation - Dilan Saatoglu; Sarah L. Lundregan; Evelyn Fetterplace; Debora Goedert; Arild Husby; Alina K. Niskanen; Stefanie Muff; Henrik Jensen (Molecular Ecology, 2024)
Dispersal affects evolutionary processes by changing population size and genetic composition, influencing the viability and persistence of populations. Investigating which mechanisms underlie variation in dispersal phenotypes and whether populations harbour adaptive potential for dispersal is crucial to understanding the eco‐evolutionary dynamics of this important trait. Here, we investigate the genetic architecture of dispersal among successfully recruited individuals in an insular metapopulation of house sparrows. We use an extensive long‐term individual‐based ecological data set and high‐density single‐nucleotide polymorphism (SNP) genotypes for over 2500 individuals. We conducted a genome‐wide association study (GWAS), and found a relationship between dispersal probability and a SNP located near genes known to regulate circadian rhythm, glycogenesis and exercise performance, among other functions. However, this SNP only explained 3.8% of variance, suggesting that dispersal is a polygenic trait. We then used an animal model to estimate heritable genetic variation ( σ A 2 ), which composes 10% of the total variation in dispersal probability. Finally, we investigated differences in σ A 2 across populations occupying ecologically relevant habitat types (farm vs. non‐farm) using a genetic groups animal model. We found different adaptive potentials across habitats, with higher mean breeding value, σ A 2 , and heritability for the habitat presenting lower dispersal rates, suggesting also different roles of environmental variation. Our results suggest a complex genetic architecture of dispersal and demonstrate that adaptive potential may be environment dependent in key eco‐evolutionary traits. The eco‐evolutionary implications of such environment dependence and consequent spatial variation are likely to become ever more important with the increased fragmentation and loss of suitable habitats for many natural populations.